Analisis Pengaruh Stimulus Lingkungan Toko, Experiential Marketing, dan Perceived Product Quality terhadap Kepuasan Pelanggan dengan Keputusan Pembelian Sebagai Variabel Intervening (Studi pada Sogogi Shabu & Grill di Cibubur) - Rafi, Muhamad Arya; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of store environment stimuli, experiential marketing, perceived product quality, and purchase decisions on customer satisfaction at Sogogi Shabu & Grill in Cibubur. The population used in this study were consumers of Sogogi Shabu & Grill in Cibubur. The number of samples used in this study were 100 consumers of Sogogi Shabu & Grill in Cibubur. The analytical tool used to test the hypothesis is Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The results showed that the store environment stimuli did not have a positive and significant effect on purchase decisions and customer satisfaction. Furthermore, experiential marketing has a positive and significant effect on purchase decisions and customer satisfaction. Furthermore, perceived product quality has a positive and significant effect on purchase decisions and customer satisfaction. Furthermore, purchase decisions have a positive and significant effect on customer satisfaction